A nucleating agent for improving the crystallization behavior of polyamide and its application
By developing a polyamide crystal nucleating agent composed of metal ion complexes, polyhydroxy compounds and inorganic silicates, the problem of high cost of existing nucleating agents is solved, and a low-cost and efficient polyamide crystallization effect and a shortening of the molding cycle are achieved.
Patent Information
- Application Number
- CN202411918574.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing polyamide nucleating agents are costly, which limits their widespread use in some cost-sensitive applications, and it is difficult to effectively improve the crystallization behavior of polyamides to shorten the molding cycle.
A low-cost and efficient polyamide crystal nucleating agent is developed through coordination chelation technology and complexing technology. The nucleating agent is composed of metal ion complexes, polyhydroxy compounds and inorganic silicates, and is cross-linked using polymer coordination and hydrogen bonding.
It is achieved to significantly reduce the cost of polyamide composite materials while ensuring crystallization and mechanical properties, shorten the molding cycle of polyamide composite materials, and improve the ring tensile strength of the product.
Smart Images

Figure CN119350833B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of modified polyamide materials, and relates to a nucleating agent for improving the crystallization behavior of polyamide and its application, in particular to a polyamide composite material using the nucleating agent and the application of the polyamide composite material in the preparation of thin-walled large aspect ratio products (such as cable ties). Background Art
[0002] Nylon 6 among polyamide materials is an important engineering plastic with excellent physical and chemical properties. It is widely used in many fields, such as textile industry, automobile industry, machinery manufacturing industry, electronic and electrical industry, packaging industry and civil fields.
[0003] Shortening the molding cycle of nylon 6 is inseparable from the use of nucleating agents. The role of nucleating agents is to promote the formation and growth of crystals, including inorganic nucleating agents and organic nucleating agents. Inorganic nucleating agents include metal ions, oxides, silicates, etc., and organic nucleating agents include organic phosphonates, organic acid salts, sorbitol benzylidene derivatives, amide derivatives, etc. Inorganic nucleating agents generally have high ionization energy and strong chemical activity, and can interact with atoms or molecules on the surface of crystals through adsorption, exchange, coordination, etc., thereby promoting the formation and growth of crystals. Organic nucleating agents generally have higher molecular weights and complex chemical structures, and can form complexes with atoms or molecules on the surface of crystals, which have a stronger impact on the morphology, size and distribution of crystals.
[0004] Organic nucleating agents can promote the formation of small and uniform crystals in nylon, thus greatly improving the strength and toughness of the material. However, the relatively high price of organic nucleating agents limits their widespread use in some cost-sensitive applications.
[0005] The present invention aims to develop a low-cost and high-efficiency polyamide crystal nucleating agent by utilizing existing commercially available chemical products through coordination chelation technology and compounding technology. Summary of the invention
[0006] The purpose of the present invention is to provide a polyamide composite material and a nucleating agent for improving the crystallization behavior of polyamide, which can improve the crystallization behavior of polyamide and shorten the molding cycle of the polyamide composite material, and at the same time reduce the cost of the nucleating agent itself, thereby reducing the cost of the polyamide composite material. The present invention also provides an application of the nucleating agent and the polyamide composite material in injection molding of thin-walled products with a large aspect ratio.
[0007] The first aspect of the present invention provides a nucleating agent for polyamide, comprising a metal ion complex and a silicate, wherein the metal ion complex is obtained by a coordination reaction of a metal ion, polyethylene oxide and a polyol, wherein the metal ion, the ethylene oxide monomer in the polyethylene oxide and the polyol are reacted in a molar ratio of 1:(0.5-2):(1-8), wherein the metal ion comprises a combination of one or more selected from calcium ions, lithium ions, magnesium ions and aluminum ions; wherein the polyol is added in excess, so that the nucleating agent also comprises unreacted excess polyol, and the weight ratio of the metal ion complex, the silicate and the total amount of the polyol added is 1:(0.5-6):(0.5-6).
[0008] Preferably, the degree of polymerization of the polyethylene oxide is between 2 and 60, and more preferably between 2 and 15. The number average molecular weight of the polyethylene oxide is between 100 and 1000.
[0009] Preferably, the polyol comprises a combination of one or more selected from the group consisting of pentaerythritol, dipentaerythritol, tripentaerythritol, methyl glucose cellulose, hydroxypropyl cellulose and glycerol.
[0010] Preferably, the silicate comprises a combination of one or more selected from talc, montmorillonite, kaolinite, vermiculite, zeolite, palygorskite, diatomaceous earth and sepiolite.
[0011] Preferably, the silicate is in the form of powder, and the size of the powder is between 0.2-20 microns, more preferably between 1 and 5 microns.
[0012] A second aspect of the present invention provides a polyamide composite material, comprising polyamide and the above-mentioned nucleating agent for polyamide, wherein the weight percentage of the nucleating agent in the polyamide composite material is 0.05-2%.
[0013] Preferably, the weight content of the metal ion complex and the silicate in the polyamide composite material is between 0.1 and 1.0%.
[0014] Preferably, the polyamide comprises a combination of one or more selected from nylon 6, nylon 66, nylon 56, nylon 610 and nylon 612.
[0015] Preferably, the polyamide composite material further comprises an acid binding agent, the weight percentage of which is 0.01-0.2%, and the acid binding agent is a carbonate series acid binding agent.
[0016] More preferably, the acid binding agent comprises a combination of one or more selected from lithium carbonate, sodium carbonate, potassium carbonate, calcium carbonate and barium carbonate.
[0017] Preferably, the polyamide composite material comprises a complex stabilizer in an amount of 0.05-0.5% by weight, and the complex stabilizer is stearate.
[0018] More preferably, the complex stabilizer includes a combination of one or more selected from lithium stearate, magnesium stearate, calcium stearate, barium stearate, sodium stearate and potassium stearate.
[0019] Preferably, the polyamide composite material includes a functional auxiliary agent selected from one or more combinations of internal lubricants, external lubricants, mold release agents, melt index flow agents, antioxidants, UV inhibitors and high temperature antioxidants. In a preferred embodiment, the polyol in the nucleating agent is used as a lubricant, and the polyamide composite material does not include other lubricants except the polyol.
[0020] The third aspect of the present invention provides an application of the above-mentioned nucleating agent for polyamide or the above-mentioned polyamide composite material in injection molding thin-walled high aspect ratio polyamide products, and an application of the above-mentioned nucleating agent for polyamide in preparing glass fiber reinforced polyamide materials.
[0021] In a preferred embodiment, the thin-walled product with a large aspect ratio comprises a cable tie.
[0022] The aspect ratio of the thin-walled large aspect ratio product is greater than 2:1, preferably 10:1 to 5000:1, and more preferably 100:1 to 5000:1; the thickness is smaller than the width.
[0023] The present invention adopts the above technical solution and has the following beneficial effects:
[0024] The nucleating agent for polyamide of the present invention is compounded by metal ion complex, polyhydroxy compound and inorganic silicate, and utilizes polymer coordination and hydrogen bond crosslinking, and has application effect equivalent to that of existing high-efficiency nucleating agent (such as nucleating agent BRUGGOLENP22), while the cost is significantly reduced, thereby providing a low-cost, practical and high-efficiency compound nucleating agent. The polyamide composite material using the nucleating agent significantly reduces the cost while ensuring that the peak temperature of the melting peak is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solution of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0026] Figure 1This is a photograph of crystals of a model complex of calcium chloride and triethylene glycol in a weight ratio of 1:1.12.
[0027] Figure 2 This is a photograph of a model complex powder of calcium chloride, triethylene glycol and pentaerythritol in a weight ratio of 1:0.56:1.24.
[0028] Figure 3 This is the infrared spectrum (FTIR) of the model complex crystal of calcium chloride and triethylene glycol with a weight ratio of 1:1.12.
[0029] Figure 4 The temperature drop crystallization curves of the polyamide composite materials of Examples 1 to 9.
[0030] Figure 5 The temperature drop crystallization curves of the polyamide composite materials of Comparative Examples 1 to 8 are shown.
[0031] Figure 6 This is a photograph of the cable tie prepared in Example 11.
[0032] Figure 7 This is the ring pull test curve of the cable tie of Example 11.
[0033] Figure 8 This is the ring pull test curve of the cable tie of Comparative Example 9. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0035] Nucleating agent is one of the commonly used additives for polyamide modified materials. The role of nucleating agent is to change the crystallization behavior of resin, accelerate the crystallization rate, increase the crystallization density and promote the refinement of grain size, so as to shorten the molding cycle, improve the product transparency, surface gloss, tensile strength, rigidity, heat deformation temperature, impact resistance, creep resistance and other physical and mechanical properties.
[0036] According to the purpose and performance requirements of the product: If the product requires high strength and high heat resistance, such as in the application of automobile engine parts, a nucleating agent that can significantly improve the crystallinity and crystal morphology should be selected. For products that require high transparency, such as optical lenses, a nucleating agent that has little effect on transparency or can even improve transparency should be selected.
[0037] Consider cost factors: The prices of nucleating agents vary greatly. Under the premise of meeting performance requirements, lower-cost nucleating agents should be selected as much as possible to improve the market competitiveness of products.
[0038] Combined with different processing techniques (such as injection molding, extrusion, blow molding, etc.): There are different requirements for the dispersibility and stability of the nucleating agent. When selecting a nucleating agent, it is necessary to ensure that it can fully play its role in a specific processing technology. In practical applications, nylon nucleating agents have been widely used in various fields. In the automotive industry, the application of nylon nucleating agents enables automotive parts to have higher strength, heat resistance and dimensional stability, such as engine hoods, intake manifolds, fuel system components, etc. In the field of electronics and electrical appliances, nylon materials with nylon nucleating agents can meet the strict requirements for dimensional accuracy and electrical properties, and are used to manufacture connectors, sockets, coil skeletons and other components. In the packaging industry, nylon nucleating agents can improve the transparency and barrier properties of nylon films and extend the shelf life of items in the package.
[0039] At present, there are only a few nucleating agents for polyamide, such as BRUGGOLEN P22 and CAV102. These nucleating agents have good application effects, but their costs are relatively expensive. Based on this, this article provides a compound nucleating agent for polyamide, which significantly reduces the cost while improving the crystallization behavior of polyamide; the effect of the compound nucleating agent on the improvement of the crystallization behavior of polyamide is equivalent to that of a high-efficiency nucleating agent (such as nucleating agent BRUGGOLEN P22). The nucleating agent for polyamide is compounded by metal ion complexes, polyhydroxy compounds and inorganic silicates, and utilizes polymer coordination combined with hydrogen bond crosslinking to ensure the crystallization effect while having significantly lower costs. The specific description is as follows.
[0040] Soluble metal salts are generally hygroscopic. For example, calcium chloride and aluminum chloride can strongly absorb moisture from the air in the natural environment, accompanied by heat generation. Using these compounds alone will lead to the following consequences: (1) After absorbing water, the chloride will release metal ions and corrode the equipment; (2) The absorbed water will be released during the processing, causing the polyamide to hydrolyze and degrade during the processing; (3) Due to the heat release caused by chloride absorption, there is a potential risk of operators being scalded during the construction process. Through coordination and complexation technology, the coordination bonds are used to occupy the empty orbits of metal ions, significantly reducing the water absorption capacity of chlorides. This can not only avoid the above disadvantages, but also has the advantages of easy drying, easy operation, and convenient transportation.
[0041] A nucleating agent for polyamide, comprising a metal ion complex and a silicate, wherein the metal ion complex is obtained by a coordination complex reaction of metal ions, polyethylene oxide (calculated based on the ethylene oxide monomer contained therein) and polyols in a molar ratio of 1:(0.5-2):(1-8), wherein the metal ions include a combination of one or more selected from calcium ions, lithium ions, magnesium ions and aluminum ions; wherein the polyols are added in excess, so that the nucleating agent also includes unreacted excess polyols, and the weight ratio of the metal ion complex, silicate and the total amount of the polyols added is 1:(0.5-6):(0.5-6).
[0042] The polyol in the reaction raw material for generating the metal ion complex is added in excess, a part of which participates in the preparation of the coordination complex, that is, participates in the chemical complex reaction between the metal ion and the polyethylene oxide to generate the metal ion complex; the remaining part of the polyol is coordinated with the metal ion complex and the silicate. The weight ratio of the metal ion complex, the silicate, and the total amount of the polyol is preferably 1: (1-5): (2-6), and more preferably 1: (1-3): (2-4).
[0043] Herein, the metal ion complex includes a coordination complex generated by a chemical reaction between metal ions and polyethylene oxide and polyols, and the metal ion complex is mixed with an excess of unreacted polyols, i.e., a mixture of metal ion coordination complexes and polyols. The metal ions are mixed with other raw materials in the form of metal salts (such as their chlorides, sulfates, carbonates, etc.), such as calcium chloride, magnesium chloride, etc. The molar ratio of metal ions, polyethylene oxide (calculated based on the ethylene oxide monomers contained therein) and polyols is preferably 1: (0.5~1): (2~5).
[0044] The degree of polymerization of polyethylene oxide is between 2 and 60, and more preferably between 2 and 15. The number average molecular weight of polyethylene oxide is between 100 and 1000.
[0045] The silicate comprises a combination of one or more selected from talc, montmorillonite, kaolinite, vermiculite, zeolite, palygorskite, diatomaceous earth and sepiolite. The silicate is a powder, and the size of the powder is between 0.2-20 microns, more preferably between 1-5 microns.
[0046] A polyamide composite material comprises polyamide and the above-mentioned nucleating agent for polyamide, wherein the nucleating agent is used to improve the crystallization behavior of polyamide and shorten the molding cycle. The weight percentage of the nucleating agent in the polyamide composite material is 0.05-2%. The polyamide comprises a combination of one or more selected from nylon 6, nylon 66, nylon 56, nylon 610 and nylon 612.
[0047] The weight contents of the metal ion complex and the silicate in the polyamide composite material are respectively between 0.1-1.0%.
[0048] The polyamide composite material also includes an acid binding agent, the weight percentage of which is 0.01-0.2%, and the acid binding agent is a carbonate series acid binding agent. The acid binding agent includes a combination of one or more selected from lithium carbonate, sodium carbonate, potassium carbonate, calcium carbonate and barium carbonate.
[0049] The polyamide composite material includes a complex stabilizer, the weight percentage of which is 0.05-0.5%, wherein the complex stabilizer is a stearate, and the complex stabilizer includes a combination of one or more selected from lithium stearate, magnesium stearate, calcium stearate, barium stearate, sodium stearate and potassium stearate.
[0050] The polyamide composite material includes a functional auxiliary agent selected from one or more combinations of internal lubricants, external lubricants, mold release agents, melt index flow agents, antioxidants, UV inhibitors and high temperature antioxidants. In a preferred embodiment, the polyol in the nucleating agent is used as a lubricant, and the polyamide composite material does not include other lubricants except the polyol.
[0051] The polyamide composite material may further include glass fibers, wherein the weight percentage of the glass fibers is 10-50%.
[0052] The preparation method of the polyamide composite material comprises: weighing raw materials according to proportion, mixing them evenly, and extruding them to obtain a polyamide composite masterbatch;
[0053] Wherein, the extrusion temperature is Tm+20°C, and Tm represents the peak temperature of the DSC thermal analysis melting peak of the polyamide composite material.
[0054] An application of the above-mentioned nucleating agent for polyamide or the above-mentioned polyamide composite material in injection molding of thin-walled polyamide products with high aspect ratio. Specifically, the thin-walled products with high aspect ratio include cable ties. Herein, "thin-walled products with high aspect ratio" refers to products with aspect ratio greater than 2:1, preferably 10:1 to 5000:1, more preferably 100:1 to 5000:1, and thickness less than width.
[0055] The principles of this embodiment include: the use of metal ion complexation technology such as calcium ion is because compounds such as calcium chloride and aluminum chloride have extremely strong hygroscopicity, and the presence of water easily promotes the hydrolysis and degradation of nylon. The complex occupies the empty orbit of the metal ion through the ligand, thereby inhibiting the hygroscopicity of the compound.
[0056] The model complex was prepared using calcium chloride, triethylene glycol and pentaerythritol as raw materials. The photo of the model complex crystal of calcium chloride and triethylene glycol (the weight ratio of calcium chloride to triethylene glycol is 1:1.12) can be found in Figure 1 ; For a photo of the model complex powder of calcium chloride, triethylene glycol and pentaerythritol (the weight ratio of calcium chloride: triethylene glycol: pentaerythritol is 1:0.56:1.24), see Figure 2 The infrared spectrum (FTIR) of the model complex crystal of calcium chloride and triethylene glycol can be found at Figure 3 .from Figures 1 to 3 It can be seen that calcium chloride, polymers with ethylene oxide as monomers, and pentaerythritol can generate metal ion complexes; however, since triethylene glycol has a small molecular weight and is easy to precipitate, the following examples do not use this model complex, but instead use a complex generated by the reaction of calcium chloride, pentaerythritol, and PEG400.
[0057] The invention is described in detail below through specific examples and comparative examples.
[0058] Source of raw materials:
[0059] Nylon 6 chips (PA6): Jiangsu Yongtong New Material Technology Co., Ltd.
[0060] Pentaerythritol: Shanghai Yaoshi Trading Co., Ltd.
[0061] Polyethylene oxide (PEG400): The molecular weight of its polymer monomer (ethylene oxide) is 44 g / mol. Tianjin Zhiyuan Chemical Reagent Co., Ltd.
[0062] Anhydrous ethanol (99%): Tianjin Zhiyuan Chemical Reagent Co., Ltd.
[0063] Talc powder (particle size 2-5 microns): Shenzhen Jinhao Industrial Development Co., Ltd.
[0064] P22 (polyamide nucleating agent): Neunopril New Technology Development (Shanghai) Co., Ltd.
[0065] MMT (modified montmorillonite): Zhejiang Fenghong New Materials Co., Ltd.
[0066] Calcium chloride: Weifang Dakang Chemical Co., Ltd.
[0067] EBS (vinyl bis stearamide): Kesachenggong (Zhejiang) New Material Technology Co., Ltd.
[0068] CaSt2 (calcium stearate): Zhangjiagang Oasis New Material Technology Co., Ltd.
[0069] Antioxidant 1098: Lianlong (Tianjin) Chemical Co., Ltd.
[0070] Sodium carbonate: Nanjing Chemical Reagent Co., Ltd.
[0071] Glass fiber: China Jushi Co., Ltd.
[0072] The test methods corresponding to the performance involved in the following embodiments are as follows:
[0073] The crystallization behavior was tested by differential scanning calorimetry (DSC);
[0074] The test methods for tensile strength, elongation at break, and tensile modulus are as per ASTM D-638;
[0075] The test methods for flexural strength and flexural modulus refer to ASTM D-790;
[0076] The test method for notched impact strength is as per ASTM D-256;
[0077] The test method for the loop tensile strength of cable ties is given in UL 62275.
[0078] Examples 1 to 9
[0079] Step (1) - Preparation of calcium chloride complex: Under stirring at 60 rpm, weigh pentaerythritol, polyethylene oxide and calcium chloride as shown in Table 1, first disperse pentaerythritol and polyethylene oxide in 10 times the weight of anhydrous ethanol at room temperature, then gradually add calcium chloride to the mixed solution, continue stirring for 30 minutes, then raise the temperature, distill and remove ethanol, and obtain a white solid powder for use.
[0080] Step (2) - Preparation of nucleating agent: weigh talcum powder according to Table 1, and mix it evenly with the white solid powder obtained in step (1) to obtain a nucleating agent;
[0081] Step (3) - Preparation of polyamide composite material: Weigh nylon 6 according to Table 1, mix it with the nucleating agent obtained in step (2), and extrude it to obtain a polyamide composite masterbatch.
[0082] Comparative Example 1
[0083] In this comparative example, all raw materials are nylon 6. Comparative Example 2
[0084] In this comparative example, the nucleating agent is replaced by dipentaerythritol in an amount of 0.2 wt %, and the remaining raw materials are nylon 6. Comparative Example 3
[0085] In this comparative example, the nucleating agent is replaced by P22 with an addition amount of 0.2 wt %, and the remaining raw materials are nylon 6. Comparative Example 4
[0086] In this comparative example, the nucleating agent is replaced by MMT with an addition amount of 0.2 wt %, and the remaining raw materials are nylon 6. Comparative Example 5
[0087] In this comparative example, the nucleating agent is replaced by calcium chloride with an addition amount of 0.2 wt %, and the remaining raw materials are nylon 6. Comparative Example 6
[0088] In this comparative example, the nucleating agent is replaced by Talc, the addition amount is 0.2wt%, and the remaining raw materials are nylon 6. Comparative Example 7
[0089] In this comparative example, the nucleating agent is replaced by a composition of EBS (vinyl bisstearamide), CaSt2 (calcium stearate) and MPE (pentaerythritol), and the addition amount is 0.2 wt %, and the remaining raw materials are nylon 6. Comparative Example 8
[0090] In this comparative example, the nucleating agent is replaced by EBS, CaSt2, MPE and Talc, and the added amount is 0.2 wt %, and the remaining raw materials are nylon 6.
[0091] Performance Testing
[0092] Table 2 shows the DSC (differential scanning calorimeter) test data and mechanical property test data of the embodiments and comparative examples.
[0093]
[0094] The DSC cooling crystallization curves of the polyamide composite materials prepared in Examples 1 to 9 are shown in Figure 4 The DSC cooling crystallization curves of the polyamide composites prepared in Comparative Examples 1 to 8 are shown in Figure 5 .
[0095] Combined with Table 2 and Figures 4 to 5 Modified montmorillonite and talcum powder are both inorganic silicates. Their powders can be used as nucleating agents for polyamides and have a high nucleating effect. However, due to the large dispersion of crystal size, the toughness of polyamide is significantly reduced, which is mainly manifested in a more significant decrease in elongation at break and large dispersion of tensile and notched impact data, which is not conducive to the stability of the end product. In comparison, since organic nucleating agents have a certain compatibility with the matrix resin, they can be evenly dispersed in the matrix during the modification process. The crystal size generated during the processing is more uniform, and the performance stability of the material is better, but organic nucleating agents are generally more expensive. This paper uses the principle of metal coordination and complexation, uses a low-cost metal organic complex, which has the effect of an organic compound, and applies it to the polyamide nucleation system. By combining the two types of nucleating agents, and taking advantage of the rapid crystallization effect of inorganic nucleating agents and the uniformity of organic nucleating agents, a new type of polyamide nucleating agent system with low price and high efficiency is prepared. In particular, under the premise of ensuring that the crystallization performance and other mechanical properties are comparable to those of conventional commercially available nucleating agents, the nucleating agent of the embodiment significantly improves the notched impact strength of the polyamide composite material. Example 10
[0096] Calcium chloride, polyethylene oxide and pentaerythritol were prepared in a weight ratio of 1:0.6:2 to obtain a mixture of metal ion complex and pentaerythritol, and a polyamide composition was prepared according to the formula in Table 3, and cable tie products were produced by injection molding. Embodiment 11
[0097] Calcium chloride, polyethylene oxide and pentaerythritol were prepared in a weight ratio of 1:0.6:3 to obtain a mixture of metal ion complex and pentaerythritol, and a polyamide composition was prepared according to the formula in Table 3, and cable tie products were produced by injection molding. Comparative Example 9
[0098] Nylon 6 and commercially available cable tie masterbatch were used to prepare a polyamide composition according to the formula in Table 3, and cable tie products were produced by injection molding.
[0099] The formulations and properties of Example 10, Example 11 and Comparative Example 9 are shown in Table 3 below.
[0100]
[0101] See the photo of the cable tie prepared in Example 11. Figure 6 . Figure 7 The test curve of the ring pull test of the cable tie prepared in Example 11 is shown. Figure 8 The test curve of the ring pull test of the cable tie prepared in Example 9 is shown.
[0102] Combined with Table 3 and Figures 7 and 8 The ring tensile strength of the explosive bands of Examples 10 and 11 is significantly improved compared to the cable tie of Comparative Example 9. Example 12
[0103] Calcium chloride, polyethylene oxide and pentaerythritol were prepared in a weight ratio of 1:0.6:2 to obtain a mixture of metal ion complex and pentaerythritol, and a polyamide composite masterbatch was prepared according to the formula in Table 4. Comparative Example 10
[0104] The polyamide composite masterbatch was prepared according to the formula in Table 4.
[0105] The formulations and properties of Example 12 and Comparative Example 10 are shown in Table 4 below.
[0106]
[0107] As shown in this specification and claims, the terms "comprises" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list, and the method or device may also include other steps or elements. The term "and / or" as used herein includes any combination of one or more of the relevant listed items.
[0108] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0109] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. If there is any conflict or inconsistency between the definitions used herein and the definitions contained in other public documents, the definitions used herein shall prevail.
[0110] The above embodiment is only for illustrating the technical concept and features of the present invention, and is a preferred embodiment. Its purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and it cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A nucleating agent for polyamide, characterized in that: The invention comprises a metal ion complex and a silicate, wherein the metal ion complex is obtained by a coordination reaction of metal ions, polyethylene oxide and polyols, wherein the molar ratio of the metal ions, the ethylene oxide monomer in the polyethylene oxide and the polyols in the coordination reaction is 1:(0.5-2):(1-8), the metal ions comprise a combination of one or more selected from calcium ions, lithium ions, magnesium ions and aluminum ions, the polyols are pentaerythritol, and the silicate comprises a combination of one or more selected from talc, montmorillonite, kaolinite, vermiculite, zeolite, palygorskite, diatomaceous earth and sepiolite; wherein the polyols are added in excess, so that the nucleating agent also comprises unreacted excess polyols, and the weight ratio of the metal ion complex, the silicate and the total amount of the polyols added is 1:(0.5-6):(0.5-6).
2. The nucleating agent for polyamide according to claim 1, characterized in that The degree of polymerization of the polyethylene oxide is between 2 and 60, and the number average molecular weight is between 100 and 1000.
3. The nucleating agent for polyamide according to claim 1, characterized in that: The silicate is in the form of powder, and the size of the powder is between 0.2 and 20 microns.
4. A polyamide composite material, characterized in that: The invention comprises polyamide and a nucleating agent for polyamide according to any one of claims 1 to 3, wherein the weight percentage of the nucleating agent in the polyamide composite material is 0.05-2%.
5. The polyamide composite material according to claim 4, characterized in that: In the polyamide composite material, the weight content of the metal ion complex and the silicate is between 0.1 and 1.0%.
6. The polyamide composite material according to claim 4, characterized in that: The polyamide comprises a combination of one or more selected from nylon 6, nylon 66, nylon 56, nylon 610 and nylon 612.
7. The polyamide composite material according to claim 4, characterized in that: The polyamide composite material also includes an acid binding agent, the weight percentage of which is 0.01-0.2%, and the acid binding agent is a carbonate series acid binding agent.
8. The polyamide composite material according to claim 7, characterized in that: The acid binding agent comprises a combination of one or more selected from lithium carbonate, sodium carbonate, potassium carbonate, calcium carbonate and barium carbonate.
9. The polyamide composite material according to claim 4, characterized in that: The polyamide composite material comprises a complex stabilizer, the weight percentage of which is 0.05-0.5%, and the complex stabilizer is stearate.
10. The polyamide composite material according to claim 9, characterized in that: The complex stabilizer includes a combination of one or more selected from lithium stearate, magnesium stearate, calcium stearate, barium stearate, sodium stearate and potassium stearate.
11. The polyamide composite material according to claim 4, characterized in that: The polyamide composite material comprises a functional auxiliary agent selected from one or more combinations of an internal lubricant, an external lubricant, a mold release agent, a melt index flow agent, an antioxidant and an anti-ultraviolet agent.
12. Use of the nucleating agent for polyamide as claimed in any one of claims 1 to 3 or the polyamide composite material as claimed in any one of claims 4 to 11 in injection molding thin-walled high aspect ratio polyamide products, or use of the nucleating agent for polyamide as claimed in any one of claims 1 to 3 in preparing glass fiber reinforced polyamide materials.
Citation Information
Patent Citations
Polyamide composition for low temperature applications
CN103917600A
Complexing type nylon nucleating agent, preparation method thereof, compound containing nylon nucleating agent, and preparation method of compound
CN111269568A